2016
DOI: 10.1590/s1980-6574201600040022
|View full text |Cite
|
Sign up to set email alerts
|

An After-School, high-intensity, interval physical activity programme improves health-related fitness in children

Abstract: Health problems related to a low level of physical activity (PA) in children and adolescents have prompted research into extracurricular PA programs. This study was designed to determine the effects of two different levels of PA on the health-related fitness of school children. Ninety-four girls and boys (7-9 years) were randomly assigned to a control group (CG) or intervention group (IG). Over a 12 week study period, children in the CG participated in a similar PA program to that of a standard school physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 42 publications
0
28
0
2
Order By: Relevance
“…Study characteristics are presented as mean ± SD unless otherwise stated. Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study characteristics are presented as mean ± SD unless otherwise stated. Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25]. Five studies included boys only [13,18,23,25,27], 2 studies did not reported gender [15,22] and the 10 remaining studies included both boys and girls [11,12,14,16,19,20,21,24,26,28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations